PSYCHOLOGICAL CULTURE DEVELOPMENT IN PEDAGOGY STUDENTS - Olga V. Solovieva; Anna B. Kuzmina (Вестник Северо-Кавказского федерального университета)
The item offers the results of a research into the psychological culture of future teachers. There is also a view on the cognitive, affective, motivational, behavioral (activity), value-meaning, reflexive-perception, and creative components of the psychological culture in 1st and 4th year students majoring in various areas. The article also provides a view on the connection between the components of psychological culture and the indicators of student success (sell-efficiency and social competence). There is a description offered for a system of psychological assistance in view of shaping psychological cultural in future teachers.